The role of Cooperative Learning in Attaining Inclusive Education in the Classroom, Creativity and Innovation in Secondary schools in Mwanza Region- Tanzania - Paschal, Mahona, Joseph; Nyoni, Thobias, Thobias; Mkulu, Demetria, Gerold (My University, 2021)
Cooperative learning is a strategy that teachers can use in the classroom to help students achieve better performance and also help in building positive interaction among students, giving all the learners chances to be active in the learning process. The world today is facing challenges in attaining inclusive education for all. The aim of this study is to examine the role of Cooperative learning in attaining Inclusive Education in the classroom. During presentation the presenters will present on the importance of Cooperative learning in attaining Inclusive Education in the classroom. Also the presenter will present on the challenges that hinder cooperative Learning in attaining inclusive learning in the classroom. Lastly, this paper discusses the basic strategies that would be employed to improve Cooperative learning as the strategies to attain inclusive Education in the classroom. The study employed qualitative methods in data collection. The targeted population was teachers and students in five secondary schools, purpose sampling technique employed to select English teachers while randomly sampling to select students. This paper concludes that, in Oder to attain inclusive Education, it is a vital for every educator to attain training on how to develop cooperative Learning. Also teachers should invest more in research and accept radical changes in the teaching and learning processes.
Keywords: Cooperative learning; Creativity; Inclusive Education; Innovation